Polish: The efficiency of Polish logistics in comparison to Central and Eastern European countries, EU 11 - Demjaniuk, Regina; Świrska, Anna (Management and Administration Journal, 2021)
The importance of logistics is constantly increasing and expanding as the processes of globalization result in an increase of trade throughout the whole world, whereas the storage transport costs are still growing. In the World Bank ranking, Polish logistics has not changed its position since 2010 and in 2012 it is still positioned in 30th place among 155 countries, according to LPI (Logistics Performance Index). The LPI consists of both qualitative and quantitative measures and helps build profiles of logistic friendliness for these countries. It measures performance along the logistics supply chain within a country and offers two different perspectives: international and domestic. LPI assessment is carried out by large, medium and small companies from eight countries that are the major trading partners of the assessed country. From this evaluation, in 2012 Poland received 3.43 points on a scale of 1 to 5. The presented evaluation shows that Polish logistics faces a number of challenges in order to achieve the highest world standards. However, among the group of Central-Eastern European countries, Poland has a leading position.